Digitalisasi Pelaporan Zakat, Kepercayaan, Dan Partisipasi Muzakki : Systematic Literature Review Berbasis Prisma 2020 Dalam Kerangka Maqashid Al-Shariah - Hendarto, Deny Tri; Hadiwijayanti , Siti Syarifah; Sunarsih, Uun (Syntax Corporation, 2025)
Digital zakat reporting is increasingly viewed as a governance strategy to strengthen transparency, accountability, and public trust in zakat management organizations, thereby encouraging muzakki participation. This paper presents a systematic literature review (SLR) to synthesize empirical and conceptual evidence on the relationship between digital zakat reporting, trust, and muzakki participation, using maqashid al-shariah as an ethical governance lens. The review is reported in accordance with PRISMA 2020 (Page et al., 2021) and searches Scopus, DOAJ, Garuda, and Google Scholar for studies published between 2015 and 2025. Studies were selected via deduplication, title/abstract screening, full-text eligibility assessment, and inclusion; study quality was assessed using a concise rubric (0–10) covering methodological clarity, data/analysis adequacy, construct relevance, and sharia-compliance context. A thematic synthesis indicates that digital reporting practices (e.g., real-time dashboards, online disclosures, audit trails) tend to improve perceived transparency and accountability, which strengthens muzakki trust and intention/decision to pay zakat through formal institutions. Effects are contingent on digital literacy, personal data protection, service quality, and perceived sharia compliance. This review contributes by mapping recent research themes, proposing an integrated conceptual framework for future testing, and providing governance recommendations aligned with maqashid al-shariah.